2015
DOI: 10.1262/jrd.2015-065
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different vitrification devices and the effect of blastocoele collapse on the cryosurvival of <i>in vitro</i> produced porcine embryos

Abstract: The aim of this study was to determine the optimum conditions for vitrifying in vitro produced day 7 porcine embryos using different vitrification devices and blastocoele collapse methods. Firstly embryos were collapsed by micro-pipetting, needle puncture and sucrose with and without conducting vitrification. In the next experiment, non-collapsed embryos were vitrified in an open device using either superfine open-pulled straws (SOPS) or the CryoLoopTM system, or vitrified in a closed device using either the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
3
7
0
1
Order By: Relevance
“…In clinical settings, commercially available media are usually used to vitrify embryos because they are considered to be more stringently tested, reliable, and convenient than media prepared in‐house. Consistent with our previous findings (Bartolac et al., ), we showed that the post‐warm survival rate of day 7 IVP porcine embryos vitrified using Vitrolife media was similar to that obtained using our standard in‐house media. A previous comparison of in‐house and commercial media also found they were equally effective for vitrifying pronuclear stage human embryos (Alcolak et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In clinical settings, commercially available media are usually used to vitrify embryos because they are considered to be more stringently tested, reliable, and convenient than media prepared in‐house. Consistent with our previous findings (Bartolac et al., ), we showed that the post‐warm survival rate of day 7 IVP porcine embryos vitrified using Vitrolife media was similar to that obtained using our standard in‐house media. A previous comparison of in‐house and commercial media also found they were equally effective for vitrifying pronuclear stage human embryos (Alcolak et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our previous findings (Bartolac et al, 2015), we showed that the post-warm survival rate of day 7 IVP porcine embryos vitrified using Vitrolife media was similar to that obtained using our standard in-house media. A previous comparison of inhouse and commercial media also found they were equally effective for vitrifying pronuclear stage human embryos (Alcolak et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, forced collapse of the blastocoele cavity in both in vitro and in vivo generated bovine blastocysts prior to cryopreservation increased the number of live offspring born to recipients [25]. On the other hand, blastocoele collapse of in vitro produced porcine embryos prior to vitrification did not improve survival [26].…”
Section: Introductionmentioning
confidence: 96%
“…Salah satu upaya untuk menyeimbangkan laju pendinginan adalah dengan menggunakan carrier yang mampu memperkecil volume krioprotektan yang digunakan. Beberapa jenis carrier yang telah digunakan untuk vitrifikasi oosit adalah cryoloop, cryotop, fibreplug, electron microscop grid, dan lain-lain (Bartolac et al, 2015) Cryotop digunakan sebagai carrier untuk vitrifikasi maupun slow freezing (pembekuan lambat) baik pada oosit maupun pada embrio (Lin et al, 2010). Cryotop kit merupakan carrier dengan sistem tertutup sehingga mampu melindungi secara optimal dari kontaminasi maupun kerusakan secara fisik.…”
unclassified